2019
DOI: 10.1111/rda.13412
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chicken FSHR gene promoter and the correlations between polymorphisms and egg production in Chinese native hens

Abstract: ContentsEgg production is an important economic trait in poultry, and it is of great significance to study the key genes and functional SNPs that affect egg laying performance. Follicle‐stimulating hormone (FSH) plays an important physiological role in the reproductive performance of humans and animals by binding to its receptor (FSHR). Studies have shown that there are many transcriptional regulatory elements in the 5′ flanking region of the FSHR gene that interact with transcription factors to regulate FSHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The SNP association analysis revealed that apart from SNP 1, all the remaining SNPs had significant association with growth traits in both lines of chicken, suggesting the intrigue role of these Likewise, Bhattacharya et al, (2016) found that exons 2 and 4 of activin receptor 2A and activin receptors 2B were polymorphic and strongly associated with certain carcass traits in chicken population. Congruent with our findings, earlier studies reported significant association between single nucleotide polymorphisms and growth traits in innumerable genes among various chicken breeds (Bhattacharya, Chatterjee, Dange, & Bhanja, 2019;Li et al, 2019;Trevisoli et al, 2018).…”
Section: Impact Of Snp On Growth Traitssupporting
confidence: 88%
“…The SNP association analysis revealed that apart from SNP 1, all the remaining SNPs had significant association with growth traits in both lines of chicken, suggesting the intrigue role of these Likewise, Bhattacharya et al, (2016) found that exons 2 and 4 of activin receptor 2A and activin receptors 2B were polymorphic and strongly associated with certain carcass traits in chicken population. Congruent with our findings, earlier studies reported significant association between single nucleotide polymorphisms and growth traits in innumerable genes among various chicken breeds (Bhattacharya, Chatterjee, Dange, & Bhanja, 2019;Li et al, 2019;Trevisoli et al, 2018).…”
Section: Impact Of Snp On Growth Traitssupporting
confidence: 88%
“…SNP is a kind of efficient genetic marker based upon the variability at the nucleotide level and it has been widely used in genetic studies and breeding applications in animal species [ 24 , 25 ]. SNPs are more abundant in organisms, which have greater stability over generations and are more accurately genotyped.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the expressions of selected genes (ESR2 and FSHR) decreased in the T1 and T2 groups, possibly due to heat stress. Li et al [11] have suggested that heat stress induces granulosa cell apoptosis and reduces steroidogenic gene mRNA expressions. Previous studies on mammals have demonstrated that heat stress inhibits the development of ovarian follicles and tends to cause ovarian regression [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress directly affects ovarian function by altering folliculogenesis and the secretion of ovarian hormones, such as prolactin, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) [9]. Ovarian functions and folliculogenesis are mainly controlled by various genes, such as steroidogenic acute regulatory protein (STAR), inhibin subunit alpha (INHA), bone morphogenetic protein 15 (BMP-15), follicle-stimulating hormone receptor (FSHR), and estrogen receptors 1 and 2 (ESR1 and ESR2) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%